The Progress of Next Generation Sequencing in Preimplantation Genetic Testing - Brunet, Beatrice Chung Fat King; Toorabally, Mohammad Bilaal; Wu, Wei; Liu, Jiayin (Archives of Clinical and Biomedical Research, 2018)
Preimplantation genetic testing (PGT), the determination of an embryo’s constituency before implantation, is becoming more and more common in clinic and there has been a gradual shift in technology towards next generation sequencing (NGS). Numerous biopsy samples such as a blastomere of cleavage stage embryo, trophectoderm of blastocyst and polar bodies as well as non-invasive or low-invasive samples such as blastocoele fluid and embryo’s culture medium can be analyzed with different NGS platforms namely Roche, Illumina and Ion torrent. NGS technology has been validated and is now clinically applied to detect aneuploidies, partial or segmental aneuploidies, chromosomal aberrations including imbalanced translocations, inversion, deletion, duplication insertion and mosaicism, triploidy and single gene disorder which are often responsible for infertility and can be associated with spontaneous abortions and fetal malformations or diseases. Comprehensive chromosomal screening for all 24 chromosomes together with single gene disorder detection can be achieved at the same time in a single run using NGS and the analysis of multiple samples with different indication can be done on a single chip. NGS has the ability to detect numerical, structural and genetic abnormalities at a low cost with high efficiency and accuracy.